2023
DOI: 10.1136/bmjgh-2023-013498
|View full text |Cite
|
Sign up to set email alerts
|

Understanding rural women's preferences for telephone call engagement with primary health care providers in Nigeria: a discrete choice experiment

Nasir Umar,
Zelee Hill,
Joanna Schellenberg
et al.

Abstract: BackgroundThe COVID-19 pandemic has accelerated the use of mobile phones to provide primary health care services and maintain continuity of care. This study aims to understand rural women’s preferences for telephone call engagement with primary health care providers in Nigeria.MethodsA discrete choice experiment was conducted alongside an action research project that empowered primary health care workers to develop and implement a telephone call intervention to assess and enhance experiences with facility chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…This contrasts with findings from previous studies from Nigeria, which have reported gender preference for HCPs, particularly around vaccine service delivery and maternal healthcare. [56][57][58][59][60] While there are strong gender norms in Jigawa, 55 our finding may be due to the prescription of medical oxygen as a life-saving intervention during emergency clinical conditions in children compared with demand for vaccination or antenatal care services, which are non-emergency but essential healthcare services. Caregivers' refusal of medical oxygen and willingness to allow the child to die in peace highlight the importance of culture and religion in healthcare service utilisation-particularly in northern Nigeria, where child death is typically perceived as an act of God.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with findings from previous studies from Nigeria, which have reported gender preference for HCPs, particularly around vaccine service delivery and maternal healthcare. [56][57][58][59][60] While there are strong gender norms in Jigawa, 55 our finding may be due to the prescription of medical oxygen as a life-saving intervention during emergency clinical conditions in children compared with demand for vaccination or antenatal care services, which are non-emergency but essential healthcare services. Caregivers' refusal of medical oxygen and willingness to allow the child to die in peace highlight the importance of culture and religion in healthcare service utilisation-particularly in northern Nigeria, where child death is typically perceived as an act of God.…”
Section: Discussionmentioning
confidence: 99%